2015
DOI: 10.1080/00036846.2015.1005815
|View full text |Cite
|
Sign up to set email alerts
|

Financial liberalization, financial regulation and bank efficiency: a multi-country analysis

Abstract: This article investigates the impact of financial reforms on bank efficiency. More specifically, we distinguish between two different types of financial reforms, i.e. financial liberalization measures and measures of the quality of bank regulation and supervision (i.e. financial regulation), and study their relationship to bank efficiency separately. Moreover, we analyse whether the impact of financial liberalization on bank efficiency is conditional on the quality of regulation and supervision of the banking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…By using cost efficiency, the results showed that well-developed institutions have significant effects on bank efficiency. The findings are also supported by Hermes and Meesters (2015). The authors sampled banks from over 61 countries for the 1996-2005 period to investigate the impact of financial reform on cost efficiency.…”
Section: Literature Review Cost Efficiency In the Banking Sectormentioning
confidence: 67%
“…By using cost efficiency, the results showed that well-developed institutions have significant effects on bank efficiency. The findings are also supported by Hermes and Meesters (2015). The authors sampled banks from over 61 countries for the 1996-2005 period to investigate the impact of financial reform on cost efficiency.…”
Section: Literature Review Cost Efficiency In the Banking Sectormentioning
confidence: 67%
“…Additionally, their results suggest that higher quality of home country institutions and higher similarity between home and host country institutional quality reduce foreign bank inefficiency. Hermes and Meesters (2015) examine the impact of financial liberalization on bank cost efficiency using a multi-country sample of banks covering 61 countries for the period 1996-2005. Employing a range of domestic and international liberalization measures, they report a positive association between financial liberalization and increased bank efficiency that hinges upon the quality of bank regulation and supervision.…”
Section: A Review Of Related Literaturementioning
confidence: 99%
“…Several studies have focused on the importance of effective bank regulation and supervision. Hermes and Meesters (2015) find that the impact of financial liberalization on bank efficiency is conditional on the quality of regulation and supervision of the banking system. This result is corroborated by a study from the Sahay et al (2015), which finds evidence that financial development is positively related to the quality of the regulatory framework, as measured by compliance with Basel Core Principles on banking supervision and the Insurance Core Principles for the insurance industry.…”
Section: Financial Development and The Pros And Cons Of Financial Libmentioning
confidence: 99%
“…Factors that have been identified as prerequisites of successful financial liberalization are bureaucratic efficiency, a strong rule of law, proper contract enforcement, control over corruption and prudential regulation and supervision (Demirgüç-Kunt and Detragiache 1998;Summers 2000;Hermes and Meesters 2015).…”
Section: Introductionmentioning
confidence: 99%